The Collegiate Learning Assessment Setting Standards for Performance at a College or University - Hardison, Chaitra M. (RAND Corporation, 2009)
The Collegiate Learning Assessment (CLA) is a measure of how much students' critical thinking improves after attending college or university. This report illustrates how institutions can set their own standards on the CLA using a method that is appropriate for the CLA's unique characteristics.